DIE SUID-AFRIKAANSE JEUG IN VOORTREKKERTYDPERK - Visser, J.A. (Scientia Militaria - South African Journal of Military Studies, 2012)
The role of the South African Youth in the Voortrekker era is discussed in this article. Aspects such as education are brought into perspective with the peculiar circumstances of their lives during the Great Trek.